Quality control analyisis of crab meat products in Mitra Bersama Miniplant Bandar Surabaya, Central Lampung (Lighthouse Publishing, 2023)
In this increasingly sophisticated era of globalization, Small, Micro and Medium Enterprises (MSMEs) can be found in various places, from big cities to remote villages. This is what encourages business people to improve the quality of the products they produce in order to compete in the midst of intense competition in the business world. Mitra Bersama Miniplant is an MSME engaged in the processing of marine products, especially crabs with crab meat output. Mitra Bersama Miniplant continues to maintain and improve product quality by conducting supervision, but there is still a high level of damage that requires strict quality control to obtain high quality products. In controlling product quality, it can be done by using the Statistical Process Control analysis tool. The purpose of this study was to analyze whether the level of damage to crab meat products is still within tolerance limits or not and to determine the factors that influence the occurrence of defective products. This research was conducted for 30 days of production starting on 15 December 2022 to 15 January 2023 which obtained the result that the level of product defects was still within tolerance limits. The dominant factors that cause defects in crab meat can be seen from the cause and effect diagram, namely humans (labor), raw materials, work methods and machines. The most dominant product defect is soft crab meat (crushed) with a total of 68,03 kg of defective product. Therefore, it is expected that quality control at Mitra Bersama Miniplants will be improved again by carrying out stricter supervision of the production process, especially on labor factors, production process methods, raw materials, machinery and the environment so that the level of product defects decreases and the product remains good.